PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KURIR NARKOTIKA DALAM PERSPEKTIF KORBAN(STUDI KASUS PUTUSAN No. 41/Pid.Sus-Anak/2019/Pn.Pdg) - Chaerunisa Privalia (2021)
This study aims to determine how to protect a Childern who trapped in drug trafficking which plunged by a drug dealers. This often occurs in Indonesia because of theres a lot of adult drug dealers who take advantage of unstable and fragile Child to traffic the drugs. Child who are victims of couriers must be deprived of their rights, also the law enforcers should pay attention to appropriate steps to implement punishment for childers who are used as a drug couriers in order to enforce the law for Childerns right which have been implemented in the Child Protection Act. This study uses a normative juridical method as in researching using a case approach which uses literacy as the source of this research , aiming to find out how to protect and appropriately handle child victims of narcotics couriers. Considering the Rights of Childern who have been deprivied, more attention is needed for narcotics courier childern because improsentment is not the right solution. Key Words : Law Protection, Victims Perspection, Child, Narcotics Courier.